Aortic pressures within a giant right coronary artery aneurysm - Azriel Osherov; Enrique Gallego-Colon; Ella Shaviv; Xavier Piltz; Mohammad Kakoush; Yanai Ben-Gal (Journal of Cardiothoracic Surgery)
Abstract Background Giant coronary artery aneurysms are rare conditions with potentially devastating consequences. We report a case of the largest documented giant right coronary artery (RCA) aneurysm to date. Case presentation A 57-year-old male patient visited our outpatient clinic for abdominal pain and exertional dyspnea. Computed tomography identified a 10.2 × 9.8 cm RCA aneurysm with RCA pressure waves were similar to aortic pressures. After discussion by the cardiac team, elective resection with ligation of the proximal and distal ends of the RCA was performed due to the presence of adequate collaterals. Conclusion We highlight the challenges related to the management of patients presenting with giant coronary artery aneurysms. Optimal management strategies and outcomes for such rare cardiovascular conditions implies the need for standardised management guidelines.